Factors affecting the child's art education from the parents' point of view (Training and Practice : Journal of Educational Sciences, 2024)
In this study, we analyzed the musical activities of their children based on the answers from the 458 parents participating in the research. We tried to discover how imporant was to the parents for their children to study music, and for what reasons they picked a particular field of music. We also inquired into the kinds of effects the music education had on their children. We examined the correlations of the three forms of cultural capital with the children's participation in music education. We were also looking for correlations between the parents' artistic activities (musical activities, playing instruments) and their children's participation in music education. In addition to descriptive statistical procedures, the data was analyzed using factor analysis and cross-tabulation analysis.
Keywords: cultural capital of the parents; motivation in music studies